Review of the status of 20 digital libraries - Meyyappan, N. (2000)
Reviews the current status of 20 digital libraries around the world: twelve from the USA, three from the UK, two from Australia, one from New Zealand, one from Singapore and one from Canada. Concludes that while digital libraries to date have been quite useful, there is need for further improvements in terms of user interfaces and information facilities. Notes that two types of digital libraries are likely to emerge in future viz. subject- and document-specific digital libraries that will cater for specific subjects and types of information; and secondly hybrid libraries that will link the traditional libraries with its online public access catalogue (OPAC), CD-ROM and on-line databases to the world of digital libraries and virtual libraries or gateways.